Botanical Aspects, Phytochemicals and Health Benefits of Andaliman (Zanthoxylum acanthopodium) - Natasutedja, Alfredo Oktavianto; Lumbantobing, Erika; Josephine, Emita; Carol, Lioni; Junaedi, Decky Indrawan; Normasiwi, Suluh; Putra, Agus Budiawan Naro (Indonesia International Institute for Life Sciences, 2020)
Andaliman (Zanthoxylum acanthopodium) is a specialty spice widely found in the Provinces of North Sumatra and Aceh, Indonesia. The fruit is usually used by Batak people in North Sumatra as a food ingredient to cook Batak’s cuisine such as arsik, tombur, and naniura. It is also used as one of the ingredients to make Indonesian spicy sauce called sambal. Andaliman fruit is reported to eliminate the undesirable smell in fish and raw meat. Moreover, it could also reduce total volatile base nitrogen content in fish which helps to prevent spoilage. Furthermore, andaliman has been reported to contain bioactive compounds which act as antioxidant, antimicrobial, anti-inflammatory, anti-aging, anti-acne, and anti-halitosis effects. This review focuses on the botanical aspects of and health potential exhibited by andaliman.